10 Hz Amplitude Modulated Sounds Induce Short-Term Tinnitus Suppression - Neff, Patrick; Michels, Jakob; Meyer, Martin; Schecklmann, Martin; Langguth, Berthold; Schlee, Winfried (Frontiers in Aging Neuroscience, 2017)
Acoustic stimulation or sound therapy is proposed as a main treatment option for chronic subjective tinnitus. To further probe the field of acoustic stimulations for tinnitus therapy, this exploratory study compared 10 Hz amplitude modulated (AM) sounds (two pure tones, noise,music and frequency modulated (FM) sounds) and unmodulated sounds (pure tone, noise)regarding their temporary suppression of tinnitus loudness. First, it was hypothesized that modulated sounds elicit larger temporary loudness suppression (residual inhibition) than unmodulated sounds. Second, with manipulation of stimulus loudness and duration of the modulated sounds weaker or stronger effects of loudness suppression were expected, respectively.We recruited 29 participants with chronic tonal tinnitus from the multidisciplinary Tinnitus Clinic of the University of Regensburg. Participants underwent audiometric, psychometric and tinnitus pitch matching assessments followed by an acoustic stimulation experiment with a tinnitus loudness growth paradigm. In a first block participants were stimulated with all of the sounds for 3 minutes each and rated their subjective tinnitus loudness to the pre-stimulus loudness every 30 seconds after stimulus offset. The same procedure was deployed in the second block with the pure toneAM stimuli matched to the tinnitus frequency, manipulated in length (6 minutes), and loudness(reduced by 30 dB and linear fade out). Repeated measures mixed model analyses of variance(ANOVA) were calculated to assess differences in loudness growth between the stimuli for each block separately.First, we found that all sounds elicit a short-term suppression of tinnitus loudness (seconds to minutes) with strongest suppression right after stimulus offset (F(6,21)=3.74, p<0.01). Second,similar to previous findings we found that amplitude modulated (AM) sounds near the tinnitus frequency produce significantly stronger tinnitus loudness suppression than noise (vs. Pink noise:t=-4.22, p<0.0001). Finally, variants of the AM sound matched to the tinnitus frequency reduced in sound level resulted in less suppression while there was no difference observed for a longer stimulation duration. Moreover, feasibility of the overall procedure could be confirmed as scores of both tinnitus loudness and questionnaires were lower after the experiment (tinnitus loudness:t=2.77, p<0.01); Tinnitus Questionnaire: t=2.06, p<0.05; Tinnitus Handicap Inventory: t=1.92, p=0.065).Taken together, these results imply that AM sounds, especially in